Observer-Based PID Security Control for Discrete-Time T-S Fuzzy Systems under Distributed Dynamic Event-Triggered Mechanism - Sisi Lin; Mengzhuo Luo; Shouming Zhong; Kaibo Shi; Xingxu Tan (Discrete Dynamics in Nature and Society)
This study addresses the observer-based proportional-integral-derivative (PID) security control problem for nonlinear discrete-time fuzzy systems subject to deception attacks. In order to reduce the burden of communication, a distributed dynamic event-triggered mechanism (DETM) is proposed, and each sensor node is equipped with an event-trigger generator. A new discrete-time Takagi–Sugeno (T-S) fuzzy model is established, in which both DETM and deception attacks are taken into consideration. Then, based on Lyapunov stability theory, the sufficient conditions for the input-to-state stability (ISS) are proposed, and the desired fuzzy PID controllers are given. Finally, a simulation example is provided to show the usefulness of the proposed approach.